2021
DOI: 10.18502/ijps.v16i3.6256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Salivary Levels of Cortisol and Sleep Quality of Hemodialysis Patients: A Randomized Clinical Trial

Abstract: Objective: The aim of this study was to investigate the effects of exogenous melatonin on the quality of sleep in patients undergoing dialysis and to investigate its mechanism for the regulation of total circadian rhythm and salivary levels of cortisol in hemodialysis patients admitted to Pange Azar hospital in Gorgan in winter of 2017. Method: This was a double-blind randomized clinical trial. Samples were transferred to the laboratory by maintaining the cold chain. Then, the patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Night shift work is associated with disrupted melatonin production [ 51 ]. Melatonin can reduce salivary cortisol levels in haemodialysis patients at night [ 52 ]. Cortisol is a key player in the circadian system [ 53 ] and a critical secondary messenger between the central clock and all peripheral clocks [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Night shift work is associated with disrupted melatonin production [ 51 ]. Melatonin can reduce salivary cortisol levels in haemodialysis patients at night [ 52 ]. Cortisol is a key player in the circadian system [ 53 ] and a critical secondary messenger between the central clock and all peripheral clocks [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that patients on haemodialysis frequently had abnormal diurnal cortisol rhythm and experienced worse quality of sleep compared to healthy individuals ( 31 ). Further data on the interaction between evening cortisol and sleep quality is provided by a short placebo-controlled trial of evening melatonin administration in patients on haemodialysis ( 144 ). The results show a significant improvement in PSQI, along with a reduction in salivary cortisol that is proportionally greater at night-time than in the morning.…”
Section: Disturbances In Endogenous Cortisol Regulation and Their Rel...mentioning
confidence: 99%
“…This contradictory result has blurred the role of serum PTH level in the sleep disturbance associated with MHD. Furthermore, studies have shown that diet regulation and melatonin can improve the sleep quality of MHD patients ( 16 , 17 ). These lines of evidence suggest that there are many factors associated with sleep disturbance in MHD patients, and the role of some factors, such as age and PTH, needs to be confirmed by more studies.…”
Section: Introductionmentioning
confidence: 99%